2015
DOI: 10.1016/j.otsr.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of posterior cervical fixation

Abstract: The research considers that spinal surgeon should first consider using the TS technique to treat cervical TCI. If PS technique is used, we should eventually prolong the need for external bracing in order to reduce the higher risk of fracture on fixation devices. If LS technique is used, we should add anterior cervical operation for acquire a better immediate stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…Pedicle screw insertion also induces residual stresses and stress concentrations that superimpose with cyclic loads to contribute to local tissue failure. These stresses are highest at the cap‐rod‐screw interface, as we demonstrate using beams‐on‐elastic‐foundation and thick‐wall pressure vessel theory. Reported yield stresses for spinal trabecular bone range from 3 to 96 MPa .…”
Section: Discussionsupporting
confidence: 58%
“…Pedicle screw insertion also induces residual stresses and stress concentrations that superimpose with cyclic loads to contribute to local tissue failure. These stresses are highest at the cap‐rod‐screw interface, as we demonstrate using beams‐on‐elastic‐foundation and thick‐wall pressure vessel theory. Reported yield stresses for spinal trabecular bone range from 3 to 96 MPa .…”
Section: Discussionsupporting
confidence: 58%
“…Pedicle screw insertion also induces residual stresses and stress concentrations that superimpose with cyclic loads to contribute to local tissue failure. These stresses are highest at the cap-rod-screw interface, 47,48 as we demonstrate using beams-on-elastic-foundation and thick-wall pressure vessel theory. Reported yield stresses for spinal trabecular bone range from 3 to 96 MPa 49,50 .…”
Section: Discussionsupporting
confidence: 50%
“…In previous studies, posterior cervical fixation techniques have been developed, compared and validated in the long-term clinical relevant setting and biomechanical tests: (1) LS fixation technique: Heller et al [ 33 ] suggested that the LS technique reconstructed the stability of the middle and posterior column of the lower cervical spine by penetrating the bilayer cortex with greater pullout strength than the monolayer cortex. What’s more, screw inserted by LS technique had high stress concentration at the actual caprod-screw interface, but less than 100 MPa of von Mises stress [ 34 ]. The LS fixation constrained motion in flexion as a tension band and limits motion in extension to some extend due to rigidity of rods, instead of constraining the motion in axial rotation like most pedicle screw fixations [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The technique is based on the pedicle insertion screw with good three-column holding power. In addition, the ROM of the model after the reconstruction of three-column damage was significantly reduced, that is, the stability was significantly increased [ 34 ]. (3) TS fixation technique: TS technique has been used as an alternative technique to achieve posterior cervical spine stability in the lower cervical spine [ 30 ].…”
Section: Discussionmentioning
confidence: 99%